The predictive value of serum uric acid in development of acute kidney injury and mortality in patients with sepsis - Doaa Atef Moubarez (Society of Diabetic Nephropathy Prevention, 2022)
Introduction: Acute kidney injury (AKI) and sepsis are significant causes of morbidity and mortality in intensive care units. Therefore, early screening of high-risk individuals is critical for preventing AKI and improving outcomes. Objectives: To examine the possible involvement of uric acid in predicting AKI and mortality in septic patients. Patients and Methods: A prospective study recruited 400 patients with sepsis based on the quick Sequential Organ Failure Assessment (qSOFA) criteria who were hospitalized in the intensive care unit (ICU). Patients were categorized into two groups depending on their uric acid levels; those with a serum uric acid ≥7 mg/dL and those with a serum uric acid <7 mg/dL. Results: A total of 400 septic patients were included in this study. Among them, 52.5% (210/400) patients had hyperuricemia during admission to the ICU. A total of 177/400 (44.2%) patients developed AKI. The likelihood of having hyperuricemia in association with AKI was 65.6%. Meanwhile, the likelihood of having a uric acid level of less than 7 mg/dL in association with AKI was 23.9% (P<0.001). The mortality rate in the hyperuricemia group was substantially greater than in the normal uric acid level group (P<0.001). Uric acid levels higher than 7 mg/dL were significantly associated with AKI by multivariate logistic regression (P= 0.002). Receiver operating characteristic (ROC) curves revealed that uric acid has a high predictive value for AKI and ICU mortality in patients with sepsis. Conclusion: Serum uric acid could be a marker to predict AKI and mortality in patients with sepsis.